The Role of Colour Doppler of Carotid Arteries in Cerebrovascular Insufficiency - Pasha, S Mahbub (Asian Journal of Medical Radiological Research, 2019)
Background: Cerebrovascular accidents constitute a major cause of adult mortality. The principal indication for cerebrovascular Doppler examination is stroke prevention. Colour Doppler sonography is a sensitive method for detection of atherosclerotic plaque and provide considerable information about the extent and severity of plaque as well as the resulting diminution of arterial lumen. The main strengths of Sonography of carotid arteries are patient comfort, lack of risk and accuracy in detecting carotid stenosis. Subjects and Methods: The study was carried out on 40 individuals, among them 20 were symptomatic cases suspected of cerebrovascular insufficiency considered as cases and the other 20 asymptomatic cases with unrelated diseases but having one or the other risk factors for cerebrovascular disease were taken as controls. A detailed clinical history, CNS examination findings and evidence of hypertension, diabetes mellitus, hyperlipidemia and ischemic heart disease were noted. Results: Significant stenosis i.e., >40% was found in 12 (60%) of the cases & in 4(20%) asymptomatic controls. Peak systolic velocity ratio showed significant stenosis in 12(60%) of symptomatic cases and in 4(20%) of asymptomatic controls. Plaque characteristics showed 9 hyperechogenic, 8 calcific, 4 low echogenic and 5 moderate or heterogeneous plaques. Conclusion: The role of carotid Doppler in detecting the site and morphology of atherosclerotic plaque with quantifying the amount of stenosis is very well justified. In addition carotid Doppler can also be used to assess the prognosis in potential symptomatic and asymptomatic patients with one or the other risk factors for cerebrovascular disease.